Systematic Review and Inventory of Theory of Mind Measures for Young Children - Beaudoin, Cindy; Leblanc, Élizabel; Gagner, Charlotte; Beauchamp, Miriam H. (Frontiers in Psychology, 2020)
Theory of mind (TOM), the ability to infer mental states to self and others, has been a pervasive research theme across many disciplines including developmental, educational, neuro-, and social psychology, social neuroscience and speech therapy. TOM abilities have been consistently linked to markers of social adaptation and have been shown to be affected in a broad range of clinical conditions. Despite the wealth and breadth of research dedicated to TOM, identifying appropriate assessment tools for young children remains challenging. This systematic review presents an inventory of TOM measures for children aged 0 to 5 years and provides details on their content and characteristics. Electronic databases (1983-2019) and 5 test publisher catalogues were systematically reviewed. In total, 222 measures, identified within 830 studies, were found to assess the understanding of seven categories of mental states and social situations: emotions, desires, intentions, percepts, knowledge, beliefs and mentalistic understanding of non-literal communication, and pertained to 39 types of TOM sub-abilities. Information on the measures’ mode of presentation, number of items, scoring options, and target populations were extracted, and psychometric details are listed in summary tables. The results of the systematic review are summarized in a visual framework “Abilities in Theory of Mind Space” (ATOMS) which provides a new taxonomy of TOM sub domains. This review highlights the remarkable variety of measures that have been created to assess TOM, but also the numerous methodological and psychometric challenges associated with developing and choosing appropriate measures, including issues related to the limited range of sub-abilities targeted, lack of standardisation across studies and paucity of psychometric information provided.